## Sunday, 26 April 2015

### SBI PO Quantitative Aptitude Quiz -10

Direction (Q. 1 - 5): What is the next number in the following number series.

1. 15, 358, 574, 699, 763,?

1) 812 2) 804 3) 798 4) 795 5) 790

2. 6, 17, 34, 55, 220, 251,?

1) 1502 2) 1504 3) 1506 4) 1508 5) 1510

3. 124, 235, 447, 760, 1174,?

1) 1651 2) 1664 3) 1672 4) 1689 5) 1696

4. 3600, 5500, 8100, 8800,?

1) 9900 2) 9600 3) 9400 4) 9200 5) 9100

5. 15, 18, 31, 62, 119, 210,?

1) 341 2) 343 3) 345 4) 347 5) 349

Direction (Q. 6 - 10): In each question below two equations are provided. On the basic of these you have to find out the relation between x and y. Give answer

1) if x > y 2) if x > y

3) if x < y 3) if x < y

5) if x = y or no relation can be established between x and y.

6. I. 5x + 3y = 59 II. 7x + 9y = 191

7. I. 6x2 – 5x + 1 = 0 II. 3y2 + 4y + 1 = 0

8. I. 3x2 – 14x + 8 = 0 II. 2y2 – 17y + 36 = 0

9. I. 6x2 – 31x + 40 = 0 II. 7y2 – 41y + 60 = 0

10. I. x2 – 19x + 84 = 0 II. y2 – 26y + 169 = 0

Answers

1. 5; +73, +63, +53, +43, …….

2. +11, x2, +21, x4, + 31, x6……….

3. 4; +111, +212, +313, +414

4. 5; x1.5, x2.5, x3.5, x4.5…….

5. 2; +22 – 1, +42 – 3, +62 – 5, + 82 – 7

6. 3; eq (II) – eq (I) x 3

17x + 9y = 191

15x + 9y = 177

2x = 14

∴ x = 7, y = 8 ie x < y

7. 1; I. 6x2 – 3x – 2x + 1 = 0

Or 3x (2x - 1) -1(2x - 1) = 0

Or (3x - 1) (2x - 1) = 0

∴ x = ,

II. 3y2 + 3y + y + 1 = 0

Or 3y(y + 1) + 1 (y + 1) = 0

Or (3y + 1) (y + 1) = 0

∴ y = -1,

8. 4; I. 3x2 – 12x – 2x + 8 = 0

Or 3x(x - 4) – (x - 4) = 0

Or (3x - 2) (x - 4) = 0

∴ x = 4,

II. 2y2 – 8y – 9y + 36 = 0

Or 2y(y - 4) -9(y - 4) = 0

Or (2y - 9) (y - 4) = 0

∴ y = 4,

9. 3; I. 6x2 – 31x + 40 = 0

Or 6x2 – 16x – 15x + 40 = 0

Or 2x(3x - 8) – 5(3x - 8) = 0

Or (2x - 5) (3x - 8) = 0

∴ x = ,

II. 7y2 – 41y + 60 = 0

Or 7y2 – 21y – 20y + 60 = 0

Or 7y(y - 3) – 20(y - 3) = 0

Or (7y - 20) (y - 3) = 0

∴ y = 3, ∴ x < y

10. 3; I. x2 – 19x + 84 = 0

Or x2 – 7x – 12x + 84 = 0

Or x(x - 7) -12 (x - 7) = 0

Or (x - 7) (x - 12) = 0

∴ x = 7, 12

II. y2 – 26y + 169 = 0

Or (y - 13)2 = 0

∴ y – 13 = 0

Or y = 13

∴ x < y

Advertisements